1997
DOI: 10.1016/s0735-1097(97)00523-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary l-Arginine Supplementation Normalizes Platelet Aggregation in Hypercholesterolemic Humans

Abstract: This double-blinded, placebo-controlled study demonstrates that dietary supplementation with L-arginine can modestly attenuate the increased platelet reactivity seen in hypercholesterolemic patients. The data are consistent with our previous studies in hypercholesterolemic animals, demonstrating that L-arginine restores endogenous nitric oxide activity and inhibits platelet aggregation. Enhancement of endogenous nitric oxide activity is a potential novel therapeutic strategy worthy of further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
100
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(103 citation statements)
references
References 50 publications
1
100
0
2
Order By: Relevance
“…[3][4][5] Both oral and local administration of the NO precursor L-arginine have been shown to restore vascular NO activity in animals and in humans, 10,17 and this is associated with reduced endothelial adhesiveness for monocytes and inhibition of intimal monocyte accumulation in the vessel wall. 7,11 By contrast, longterm administration of NO synthase antagonists augments endothelial adhesiveness for monocytes and accelerates atherogenesis.…”
Section: No Inhibits Monocyte Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Both oral and local administration of the NO precursor L-arginine have been shown to restore vascular NO activity in animals and in humans, 10,17 and this is associated with reduced endothelial adhesiveness for monocytes and inhibition of intimal monocyte accumulation in the vessel wall. 7,11 By contrast, longterm administration of NO synthase antagonists augments endothelial adhesiveness for monocytes and accelerates atherogenesis.…”
Section: No Inhibits Monocyte Bindingmentioning
confidence: 99%
“…Endothelium-derived NO has been shown to antagonize key processes involved in atherogenesis and restenosis. NO inhibits monocyte adherence and chemotaxis, 3 platelet adherence and aggregation, 4,5 and vascular smooth muscle proliferation. 6 Enhancement of NO activity in hypercholesterolemic rabbits reduces monocyte adherence and accumulation, whereas inhibition of NO activity enhances endothelial adhesiveness for monocytes and increases the extent of lesion formation.…”
mentioning
confidence: 99%
“…Our study was not designed to determine whether baseline platelet aggregation was increased in patients with atherosclerosis compared with those without, although previous studies [67][68][69][70][71][72][73][74][75][76][77] have demonstrated increased baseline ex vivo platelet aggregation in patients with atherosclerosis and those with hypercholesterolemia. Our observations that stimulation of endothelial NO activity produces less inhibition of platelet aggregation in patients with atherosclerosis, coupled with previous observations of increased platelet aggregation in this group, suggest that decreased NO activity during stress, a powerful stimulus for endothelial NO production, may contribute to this observed difference in patients with atherosclerosis.…”
Section: Study Limitationsmentioning
confidence: 99%
“…All three have been associated with beneficial effects, including improvements in vascular function, systemic inflammatory profile, local inflammation at lesional sites, and an improved platelet profile (4)(5)(6). However, several clinical investigations, particularly long-term studies, have failed to translate these observations into clinical benefit (e.g., refs.…”
mentioning
confidence: 99%